Impact and cost of the peer-led Students As LifeStyle Activists programme in high schools. (February 2020) - Shrewsbury, Vanessa A; Venchiarutti, Rebecca L; Hardy, Louise L; Foley, Bridget C; Bonnefin, Amy; Byth, Karen; Hayes, Alison J; Flood, Victoria M; Steinbeck, Katharine S; Baur, Louise A; Shah, Smita
Objective: To determine the impact of a peer-led, school-based programme (Students As LifeStyle Activists; SALSA) on energy balance–related behaviours (EBRBs) in Grade 8 students, and the cost of implementing the programme. Design: Pre–post test Setting: High schools in New South Wales, Australia. Methods: Grade 10 students (15- to 16-year-olds) were trained by university students to deliver four lessons on healthy eating and physical activity to Grade 8 students (13- to 14-year-olds). Students completed an online questionnaire pre–post lessons on EBRBs and intentions to change EBRBs over the next month. Items included fruit, vegetable and sugar-sweetened beverage (SSB) intake, frequency of eating breakfast, participation in moderate-to-vigorous physical activity (MVPA) and school-day recreational screen-time. Pre–post changes were analysed using generalised estimating equations, adjusted for clustering. Standard methods were used to estimate implementation costs. Results: In total, 2, 056 Grade 8 students from 23 high schools participated. Significant changes included 5.2% increase in eating >2 fruit serves/day ( p < .001), 2.5% increase in eating >4 vegetable serves/day ( p < .05), a 4.3% increase in drinking <1 cup/day of SSB ( p < .001) but limiting screen-time <2 hours/day decreased by 4.4% ( p < .001). There were significant improvements in students' intentions to change EBRBs over the next month, with the exception of MVPA. The average actual cost of implementing the SALSA programme in 2014–2015 was AU1, 388 (US958) per school and AU9.97 (US6.88) per student. Conclusion: The SALSA peer education programme had a positive impact on most of the dietary EBRBs examined. The cost evaluation showed that it is a relatively low-cost programme to implement.